THE ROLE OF SOCIAL PROTECTION SYSTEM IN DEALING WITH CHILDREN VICTIMS OF SEXUAL ABUSE (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The social protection system is a dynamic category that has been continuously changing for a long time in order to adapt to the new social context and the current problems imposed by modern living. The rapid industrialization, the poverty, and the limited access to social services, sometimes deprive the family and the primary social security network of the opportunity to provide quality and timely care when it comes to the needs of their members, especially children. That is why Social work centers as guardianship authorities and basic social protection services in the local community are most called upon to provide assistance and support to children with endangered development as a result of various forms of abuse, but also to take actions in order to prevent the occurrence of victimization.Hence, the basic idea of ​​this paper is to provide a detailed overview of the Social work centers authorizations in dealing with children victims of sexual violence and exploitation and to determine their role and importance in realizing the concept of child welfare. In this regard, the authorizations that according to their content can prevent the occurrence of this type of crimes in order to enable early detection and treatment of the child exposed to risk of abuse, will be equally considered as well as the intervention measures that the centers are authorized to take on, in order to ensure comprehensiveness and continuity in all phases of child protection from victimization.
Keywords: sexual abuse, children, social work centers, social protection, treatment, rehabilitation